KONFLIK SOSIAL TRADISI PACU JALUR DI DESA TOAR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Agus Nardi; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Conflict constitutes discrepancy relationship among two parties or more (individual or group) one that has, or perceiving has, given targets but covered by thinkings, feel, or conduct that don't collateral. On year 2013, at Toar's Village happens tradition social Conflict pacu jalur outside performing. berdasakan usufructs that research conflict what do happen to cause by internal factor that meiputi communication factor, economic factor, and politics factor. Mark sense conflicting trigger factor causing conflicting silvan governance with society, conflict among juvenile humanity, and old conflict with young. Besides marks sense conflicting internal factor also be triggered by external factor that because of pacu's competition openness jalur. Conflict not also despite some bodies actor which have ndidvidu's aim and behalf and its group.This research constitute kualitatif eksploratif's research that gets case study character, one that as subject in observational it is determined bases subject involvement in band activity at Silvan Toar and subject constitutes village governance. In does data collecting, data collecting tech utilizes interview, observation, and documentation. To analyse permaslahan in observational it utilizes analisis kualitatif and will describe descriptive ala in do its writing.Key word: Social conflict, Pacu's tradition Jalur